2006
DOI: 10.1021/es051007p
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity for Degradation of Nitrogen Oxides over Visible Light Responsive Titania-Based Photocatalysts

Abstract: This study investigates photocatalytic degradation of nitrogen oxides overtitania-based photocatalysts illuminated by ultraviolet and visible light. The TiO2 photocatalyst was synthesized in a sol-gel process using titanium butoxide as the precursor. After calcination between 150 and 300 degrees C, the synthesized TiO2 responded strongly to visible light photocatalytically degrading NO(x), probably because of the existence of carbonaceous species that act as sensitizers. The optimum calcination temperature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 16 publications
1
62
0
2
Order By: Relevance
“…In previous studies, HONO (Gustafsson et al, 2006;Ndour et al, 2008;Monge et al, 2010;Beaumont et al, 2009) and NO (Ohko et al, 2008;Monge et al, 2010) in the gas phase as well as nitric acid/nitrate anion on the surface (e.g. Dalton et al, 2002;Devahasdin et al, 2003;Lin et al, 2006;Ndour et al, 2008;Negishi et al, 1998;Ohko et al, 2008) were observed as the NO 2 + TiO 2 reaction products. In the present study we have observed HONO, NO and, in addition, N 2 O to be released into the gas phase as a result of the heterogeneous reaction of NO 2 with TiO 2 surface.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In previous studies, HONO (Gustafsson et al, 2006;Ndour et al, 2008;Monge et al, 2010;Beaumont et al, 2009) and NO (Ohko et al, 2008;Monge et al, 2010) in the gas phase as well as nitric acid/nitrate anion on the surface (e.g. Dalton et al, 2002;Devahasdin et al, 2003;Lin et al, 2006;Ndour et al, 2008;Negishi et al, 1998;Ohko et al, 2008) were observed as the NO 2 + TiO 2 reaction products. In the present study we have observed HONO, NO and, in addition, N 2 O to be released into the gas phase as a result of the heterogeneous reaction of NO 2 with TiO 2 surface.…”
Section: Discussionmentioning
confidence: 94%
“…In several previous studies (e.g. Lin et al, 2006;Ohko et al, 2008) it was observed that the photocatalytic activity of the TiO 2 film can be fully regenerated after rinsing with water. In the present work, we have observed similar behaviour: the deactivated TiO 2 sample was regenerated after being immersed in water.…”
Section: Discussionmentioning
confidence: 94%
“…This process involves a solid semiconductor catalyst, most often anatase titanium dioxide (TiO 2 ), which is activated with ultraviolet light of the appropriate wavelength. To date, a number of researchers have investigated the dynamics of the photocatalysis of nitrogen oxides [2][3][4][5][6][7][8]. Photocatalytic oxidation of NO x offers the following distinctive advantages: (1) no extra reactants are required and (2) NO x is converted to nitrates, a significantly less harmful material.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic NO(g) oxidation with O 2 (g) was used as a model reaction [27][28][29][30][31][32]. Fig.…”
Section: Structural Characterization Of Polymer-templated Tio 2 Micromentioning
confidence: 99%